Characterization of 16S rRNA and internal transcribed spacer (ITS) region gene sequencing of the Aeromonas species isolated from cultured freshwater fishes - Khairul Parman, Diyana Nadhirah (2013)
The Aeromonas species are significantly found mostly on freshwater fishes that cause of disease outbreak that could not be easily control and determine their species in a rapid time. Twenty-two of Aeromonas strains isolated from diseased freshwater fishes were identified by using the 16S rRNA and Internal Transcribed Spacer (ITS) region gene sequencing. Thus all these strains were sequenced then performed a phylogenetic analysis by comparing the sequences which obtain from the BLASTn program by using methods of neighbor-joining and bootstrap value to compute the powerful topology. According to this study, the gene sequences ranged fragment size for 16S rRNA was 1500 bp and the Internal Transcribed Spacer (ITS) region was between 1000 bp to 1200 bp. All these 22 strains were identified up to genus level by 16S rRNA gene as A. hydrophila (15), A. veronii (7). However, ITS gene sequencing showed identification up to the species level as the A. hydrophila (14), A. veronii (8). Therefore, this PCR method has found to be simple, easy to perform and faster in identified the Aeromonas species. Moreover it can be used efficiently for regular monitoring of Aeromonas species when an outbreak happens.